The female athlete triad - Deimel, J. F.; Bradley, J.; Dunlap, J. (Clinics in Sports Medicine, 2012)
The Triad Consensus Conference in 1992, conducted by the American College of Sports Medicine (ACSM) task force, originally defined the "female athlete triad" as disordered eating, amenorrhea, and osteoporosis. Since that time, there have been many national and international task forces and health initiatives active in this field as the number of women athletes has continued to grow. Further investigation has lead to the current definition of the "female athlete triad": low energy availability (with or without eating disorders), menstrual dysfunction, and altered bone mineral density (BMD). This new position stand emphasizes efforts to research the underlying causes of this syndrome, as well as highlights the role of low energy availability as the key disorder among the triad. It is important to note that a vast minority of athletes diagnosed with this syndrome actually manifests all three components to the same degree simultaneously. Rather, the "triad" is best understood as a continuum ranging from health to disease of each disorder: energy availability, menstrual function, and bone density. At any one time, affected athletes move between the points at varying rates according to their individual experience. Because of the dire consequences associated with both the physical and mental health of the athlete affected by the triad, preventative measures are crucial to curbing the progression of this multifaceted syndrome.